Effect of Peganum harmala seeds extract on the hepatic tissue structure and fetus of mice - Samira Musa Sasi; Al ghoul, Nagia; Awayn, Nuri; El ghoul, Ahmed; Prastiya, Ragil (Universitas Airlangga, 2023)
Peganum harmala is one of the most used plants for the treatment of many diseases. Its effective compounds have pharmaceutical and medicinal properties. This study aims to determine the effect of aqueous extract of harmala plant seeds on body and liver weight, aspartate aminotransferase (AST), alanine transaminase (ALT), and the histological structure of liver of mice, as well as the size of the fetuses sired by treated mice. Sixteen adult male mice were divided into two groups of eight. The first group (control) was given distilled water orally, while the second group received the aqueous extract of harmala seeds at a dose of 300 mg/kg bw for three weeks. three untreated females were housed with one treated male for mating. At the end of the treatment, six male mice of each group were weighed and killed. Liver was extracted, weighed and its enzymes were measured. Also, sections of the liver were prepared for histological examination. The results showed a decrease in the body weight of the treated mice and a significant increase in the average weight of the fetuses compared with the control group, as well as marked changes in the hepatic tissue structure. There was no impact of the extract on fetal body length, liver weight and hepatic enzymes (AST and ALT) of treated mice. Further studies should be conducted to determine a safe dose that does not affect any organ in the body, so that it can be used for the treatment of many diseases.